2019
DOI: 10.1096/fj.201900722r
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic niches are endowed with a protumorigenic mechanism that supersedes the protective function of PTEN

Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide and is characterized by a fast-paced growth. Like other solid tumors, the HNSCC growth rate results in the development of hypoxic regions identified by the expression of hypoxia-inducible factor 1a (HIF-1a). Interestingly, clinical data have shown that pharmacological induction of intratumoral hypoxia caused an unexpected rise in tumor metastasis and the accumulation of cancer stem cells (CSCs). However, little is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…During tumor growth, most solid tumors undergo hypoxia, which is responsible for a more aggressive tumor behavior [ 108 , 114 ] and resistance to radio- and chemotherapy because hypoxia promotes the CSC properties associated with EMT, maintains their plasticity, stimulates early EMT by suppressing E-cadherin and induces unfolded protein response (UPR) [ 61 , 64 , 111 , 114 ]. The effect of hypoxia on cells is controlled by a family of transcriptional regulators, hypoxia-inducible factors (HIF) [ 61 , 108 , 109 ], which can also inhibit cellular apoptosis [ 30 ].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…During tumor growth, most solid tumors undergo hypoxia, which is responsible for a more aggressive tumor behavior [ 108 , 114 ] and resistance to radio- and chemotherapy because hypoxia promotes the CSC properties associated with EMT, maintains their plasticity, stimulates early EMT by suppressing E-cadherin and induces unfolded protein response (UPR) [ 61 , 64 , 111 , 114 ]. The effect of hypoxia on cells is controlled by a family of transcriptional regulators, hypoxia-inducible factors (HIF) [ 61 , 108 , 109 ], which can also inhibit cellular apoptosis [ 30 ].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
“…Little is known about the molecular pathways involved, although CSC accumulation has shown that the tumor suppressor gene PTEN is downregulated. Hypoxia-driven PTEN deregulation also causes HIF-1α activation and mTOR signaling along with EMT induction [ 114 ].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low prevalence of CSCs (1–3%), this subpopulation has a high resistance to conventional therapy due to its ability to self-renewal, differentiation, and tumorigenicity. Recent evidence indicates that hypoxic niches modify the CSC and promote the EMT-like phenotype under the deregulation of phosphatase and tensin homolog (PTEN) [ 86 ]. Interestingly the metabolic switch induced for hypoxia also contributes to it regulating certain genes related to CSCs, through increased secretion of exosomes [ 87 ].…”
Section: Impact Of Metabolic Reprogramming Driven-hypoxia On Tumormentioning
confidence: 99%
“…The cell culture was sealed inside a plastic bag with an O 2 absorber and an O 2 sensor. Upon reaching hypoxia, an O 2 concentration below 2%, a clip was used to separate the cells in cultivation from the O 2 absorber hermetically, thus keeping the O 2 concentration within the desired area stable [14] (Figure 1). All samples were submitted to hypoxia for 12 hours.…”
Section: Hypoxia Chambermentioning
confidence: 99%